2022
DOI: 10.3390/cells11081277
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Hnrnpk Gene Causes Infertility in Male Mice by Disrupting Spermatogenesis

Abstract: HnRNPK is a heterogeneous nuclear ribonucleoprotein (hnRNP) that has been firmly implicated in transcriptional and post-transcriptional regulation. However, the molecular mechanisms by which hnRNPK orchestrates transcriptional or post-transcriptional regulation are not well understood due to early embryonic lethality in homozygous knockout mice, especially in a tissue-specific context. Strikingly, in this study, we demonstrated that hnRNPK is strongly expressed in the mouse testis and mainly localizes to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…5E), implicating this subset of genes as direct targets. Among the 76 proteins, 21 were RNA-binding proteins (RBPs), 10 of which were suggested to be involved in spermatogenesis (Kuroda et al 2000, Yang et al 2012, Chapman et al 2013, Fukuda et al 2013, Legrand et al 2019, Sechi et al 2019, Liang et al 2021, Tian and Petkov 2021, Wang et al 2022, Xu et al 2022); 8 were involved in mitochondrial function; and 4 were calcium channel activity-related proteins (Fig. 5F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5E), implicating this subset of genes as direct targets. Among the 76 proteins, 21 were RNA-binding proteins (RBPs), 10 of which were suggested to be involved in spermatogenesis (Kuroda et al 2000, Yang et al 2012, Chapman et al 2013, Fukuda et al 2013, Legrand et al 2019, Sechi et al 2019, Liang et al 2021, Tian and Petkov 2021, Wang et al 2022, Xu et al 2022); 8 were involved in mitochondrial function; and 4 were calcium channel activity-related proteins (Fig. 5F).…”
Section: Resultsmentioning
confidence: 99%
“…We focused on SYNCRIP, HNRNPK, FUS, EWSR1, ANXA7, SLC25A4, and HNRPAB, the loss of which showed the greatest influence on the phenotype of the Iqch KO mice. Specifically, SYNCRIP, HNRNPK, FUS, EWSR1, and HNRPAB are RBPs that are linked to spermatogenesis by controlling mRNA translation or spermatid post-meiotic transcription (Kuroda et al 2000, Fukuda et al 2013, Sechi et al 2019, Tian and Petkov 2021, Xu et al 2022). ANXA7 is a calcium-dependent phospholipid-binding protein that is a negative regulator of mitochondrial apoptosis (Du et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In recent times, hnRNPK has attracted signi cant attention for its involvement in regulation of cell proliferation and differentiation in different tissues [26][27][28] . Notably, our recent study revealed a high expression level of hnRNPK protein in the mouse testis, particularly in SCs and germ cells [17,20] . Male mice with a targeted deletion of the pre-meiotic male germ speci c hnRNPK (Hnrnpk cKO) exhibited reproductive abnormalities and compromised spermatogenesis, ultimately leading to infertility [17] .…”
Section: Introductionmentioning
confidence: 90%
“…Notably, our recent study revealed a high expression level of hnRNPK protein in the mouse testis, particularly in SCs and germ cells [17,20] . Male mice with a targeted deletion of the pre-meiotic male germ speci c hnRNPK (Hnrnpk cKO) exhibited reproductive abnormalities and compromised spermatogenesis, ultimately leading to infertility [17] . Nevertheless, the exact physiological function and potential mechanism of hnRNPK in SCs with respect to spermatogenesis and male fertility remain unidenti ed.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation